ENERGY SAVING TECHNOLOGIES IN CITY LIFE - Ten Iroda Satimbayevna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
The article discusses the types of energy-saving technologies, types of renewable energy sources, their necessity in the life of the urban population, as well as improving the ecological situation in the city with the help of energy-saving technologies.